(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This passage elucidates the impact of accounting methods on financial reporting and decision-making processes within the context of Wisconsin’s government operations. It highlights the distinction between the "cash" basis of accounting, which records transactions based on cash inflows and outflows, and Generally Accepted Accounting Principles (GAAP), which provide a more comprehensive view of financial performance by recognizing accrued expenses and revenues. The discussion emphasizes how the use of cash basis accounting in Wisconsin has led to discrepancies between budgeted amounts and actual financial outcomes, resulting in deficits that affect the state’s creditworthiness. Furthermore, it underscores the legal requirement for local governments to adhere to GAAP standards, ensuring consistency and transparency in financial reporting across different governmental levels.